A novel multiscale modeling strategy of the low-velocity impact behavior of plain woven composites. (15th October 2021) - Hou, Yuliang; Meng, Liang; Li, Guohong; Xia, Liang; Xu, Yingjie
Abstract: A novel multiscale modeling strategy is proposed to investigate the low-velocity impact (LVI) behavior of plain woven composites. Initially, the effective properties of the yarn are obtained from the microscale modeling, in which a microscopic representative volume element (RVE) is constructed by considering carbon fibers and resin matrix. Meanwhile, a mesoscopic RVE is established using the internal fabric structure. Combined with the effective properties of the yarn and continuum damage mechanics (CDM) approaches, the damage initiation and evolution are predicted for the mesoscale models subjected to various loading conditions. A local homogenization approach is developed to transfer the warp and fill yarns, as well as the resin, into 0 ° and 90 ° subcells, respectively. Moreover, an equivalent cross-ply laminate (ECPL) cell is constructed by assembling these subcells, to represent the internal fabric structure. Finally, the LVI behavior of plain woven composites is investigated using the macroscale model obtained by extending the ECPL cells. The numerical results are in good agreement with the experimental measurements, confirming the reliability of the multiscale modeling strategy. The LVI damage mechanisms of plain woven composites are analyzed using the numerical simulations, indicating that the delamination and matrix-based damages are the prevailing failure modes.